Utilization without equity: investigating gendered and structural inequities in antenatal care use in rural Kebbi State, Nigeria - Egbo, Cyril Afamefuna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Antenatal care (ANC) is a proven strategy for reducing maternal and neonatal morbidity and mortality. Yet in many low- and middle-income countries (LMICs), including Nigeria, systemic and gendered barriers continue to undermine equitable utilization, particularly in rural settings. This study investigates structural and gender-based inequities influencing ANC utilization among women in rural Kebbi State, Nigeria. Methods: A cross-sectional study was conducted with 420 women in Kebbi State. Data were collected using structured questionnaires and analysed using descriptive statistics, chi-square tests, means, and standard deviations via SPSS v20. Results: Although 95.2% of respondents reported the presence of primary health centres (PHCs), service consistency was limited. Only 59% and 52.9% reported access to iron supplementation and deworming medications, respectively. Major barriers included long distances (48.8%), transport costs (41.0%), and absence of female providers (28.3%). Higher educational attainment and decision-making autonomy were significantly associated with increased ANC attendance (p<0.05). The mean number of ANC visits was 3.7 (SD±1.6), falling short of WHO recommendations, particularly among women with no formal education (mean=2.9, SD±1.4). Conclusions: The availability of ANC services does not equate to equitable access and utilization. Deep-rooted structural and gendered inequities constrain maternal healthcare utilization in rural Nigeria. Interventions must prioritize equity, gender responsiveness, and community empowerment to ensure inclusive maternal health outcomes.